Exercise mitigates Alzheimer’s disease by targeting ferroptosis driven by cellular senescence - Yu, Yuehan; Chen, Kang (Frontiers in Cell and Developmental Biology, 2026)
Ferroptosis, a regulated form of cell death driven by iron-dependent lipid peroxidation, has emerged as a critical link between cellular senescence and Alzheimer’s disease (AD). Senescent cells disrupt iron metabolism, promote peroxidation-prone lipid remodeling, and suppress antioxidant defenses, creating a pro-ferroptotic environment that accelerates neuronal degeneration. This review integrates recent mechanistic evidence demonstrating that these senescence-induced changes heighten ferroptotic susceptibility and drive AD pathology through pathways involving protein aggregation, autophagic failure, and inflammatory synaptic loss. Importantly, physical exercise has emerged as a pleiotropic intervention that counteracts these ferroptotic mechanisms at multiple levels. Exercise restores iron homeostasis, reprograms lipid metabolism to reduce peroxidation risk, reactivates antioxidant systems such as GPX4, enhances mitochondrial and autophagic function, and suppresses chronic neuroinflammation. Moreover, systemic adaptations through muscle, liver, and gut axes coordinate peripheral support for brain health. By targeting ferroptosis driven by cellular senescence, exercise not only halts downstream neurodegenerative cascades but also interrupts key upstream drivers of AD progression. These findings position ferroptosis as a therapeutic checkpoint linking aging biology to neurodegeneration and establish exercise as a mechanistically grounded strategy for AD prevention and intervention.